The Economic Benefits of Investing in Child Health - Belli, Paolo C.; Appaix, Olivier (World Bank, Washington, DC, 2013)
This paper presents a survey of the theory and the evidence on the economic impact of investing in child health. It shows that investing in the health of children is justified not only because it fulfills a basic human right, but also because it is an investment with high social and private returns. A central theme of this paper is that the relationship that links child health with economically relevant dimensions is circular-poverty contributes to disease, and poor health contributes to perpetuating poverty. The available evidence shows that almost 11 million children die every year from largely preventable diseases, and it unveils what the principal determinants of child illness are. The vast majority of children who die belong to the more disadvantaged socioeconomic groups within each country. Furthermore, the literature identifies several interventions and programs that could significantly contribute to improved child health, particularly in the areas of nutrition, communicable disease prevention and control, and education. We intuitively understand that there is a huge potential for largely positive social and economic returns on child health investments. Yet quantitative estimation of these benefits is still at an early stage. First, the association between health interventions and their social and economic consequences is multidimensional and complex. Second, the return on investment is measurable only over the long term. Third, the return is not automatic, and its magnitude is highly context-specific. For these reasons, few studies, mostly in the area of nutrition or of immunization services, have attempted to develop a full cost-benefit analysis, or to provide a quantitative measure of the benefits attainable by investing in child health. Instead, most empirical studies have focused on one of the several potential intermediate benefits of investing in child health, such as improved cognitive ability, increased school participation and attainment, and the induced demographic changes, which can be measured with greater precision.